Restoration of Aquatic Systems - Livingston, Robert (CRC Press, 2009)
Simplistic thinking would have us believe that by eliminating the loading of a given pollutant, an aquatic system will revert to its previous pristine state. This premise is without scientific verification. Besides the fact that typically very little documentation exists defining what exactly that previous pristine state was, it should be noted that biological processes are non-linear. They reflect adaptations by populations and corresponding responses of trophic organization that are not predictable by linear models of recovery.